Chemical composition, antioxidant activity and extraction optimization of Distichochlamys orlowii rhizomes - Le Hong Luyen; Nguyen Thi Linh; Le Thi Hong (Vietnam Journal of Science and Technology, 2024)
Distichochlamys orlowii is an endemic ginger species in Vietnam. The present study aimed to investigate the chemical composition, antioxidative capacity and extraction optimization of D. orlowii rhizomes (DO-R) for the first time. The results demonstrated that DO-R possessed more unsaturated fatty acids (53.10%) than saturated fatty acids (46.90%). Many unsaturated fatty acids of great health benefits were present, including trans-13-octadecenoic acid (C18:1), linoleic acid (C18:2), arachidonic acid (C20:4) and eicosapentaenoic acid (C20:5). In addition, seven essential amino acids (EAA) were detected with 41.79 ± 1.02 mg. In comparison, ten non-essential amino acids (N-EAA) were found at a much higher amount of 252.09 ± 1.06 mg in 100 g DO-R. Valine and arginine were the most abundant EAA and N-EAA in DO-R. The methanol fraction from DO-R was shown to have a higher total phenolic content (TPC = 28.85 ± 0.74 mg GAE/g DW) and total flavonoid content (TFC = 14.03 ± 0.31 mg QE/g DW) than other fractions. In addition, this extract was also the most effective antioxidative agent with an IC50 value of 168.63 ± 4.83 and 153.80 ± 8.24 µg/mL against DPPH and ABTS radical, respectively. The highest extraction yield of DO-R in methanol (95.534 ± 0.593 mg/g DW) was achieved using response surface methodology with a Box-Behnken design under the optimal parameters: a solid-liquid ratio of 1:40 g/mL, an ultrasonic power level of 80%, an extraction time of 60 min, and an extraction temperature of 58°C. In conclusion, D. orlowii can serve as a source of high-potential compounds for further pharmacological applications.